Recent Developments in Nanotechnology for Detection and Control of Aedes aegypti-Borne Diseases - Campos, Estefânia Vangelie Ramos; de Oliveira, Jhones Luiz; Abrantes, Daniele Carvalho; Rogério, Carolina Barbára; Bueno, Carolina; Miranda, Vanessa Regina; Monteiro, Renata Aparecida; Fraceto, Leonardo Fernandes (Frontiers in Bioengineering and Biotechnology, 2020)
Arboviruses such as yellow fever, dengue, chikungunya and zika are transmitted mainly by the mosquito vector Aedes aegypti. Especially in the tropics, inefficacy of mosquito control causes arboviruses outbreaks every year, affecting the general population with debilitating effects in infected individuals. Several strategies have been tried to control the proliferation of A. aegypti using physical, biological and chemical control measures. Other methods are currently under research and development, amongst which the use of nanotechnology has attracted a lot of attention of the researchers in relation to the production of more effective repellents and larvicides with less toxicity, and development of rapid sensors for the detection of virus infections. In this review, the utilization of nano-based formulations on control and diagnosis of mosquito-borne diseases were discussed. We also emphasizes the need for future research for broad commercialization of nano-based formulations in world market aiming a positive impact on public health.